2007
DOI: 10.4049/jimmunol.179.7.4711
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of TLR- and RLR-Signaling in the Immune Responses to Influenza A Virus Infection and Vaccination

Abstract: The innate immune system recognizes influenza A virus via TLR 7 or retinoic acid-inducible gene I in a cell-type specific manner in vitro, however, physiological function(s) of the MyD88- or interferon-β promoter stimulator 1 (IPS-1)-dependent signaling pathways in antiviral responses in vivo remain unclear. In this study, we show that although either MyD88- or IPS-1-signaling pathway was sufficient to control initial antiviral responses to intranasal influenza A virus infection, mice lacking both pathways fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
307
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 273 publications
(341 citation statements)
references
References 48 publications
25
307
1
8
Order By: Relevance
“…The alternative explanation of a higher level of viral replication inducing a smaller increase in these viral‐sensing TLRs also appeared unlikely 3, 4, 5, 7, 8. Our results are in line with recent mice experiments which showed that TLR activation rapidly produces virus inhibitory responses (predominantly through type I IFNs and IFN‐stimulated mechanisms), conferring protection against influenza challenge 3, 4, 10, 14. Tuvim et al .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The alternative explanation of a higher level of viral replication inducing a smaller increase in these viral‐sensing TLRs also appeared unlikely 3, 4, 5, 7, 8. Our results are in line with recent mice experiments which showed that TLR activation rapidly produces virus inhibitory responses (predominantly through type I IFNs and IFN‐stimulated mechanisms), conferring protection against influenza challenge 3, 4, 10, 14. Tuvim et al .…”
Section: Discussionsupporting
confidence: 89%
“…Increased TLR (7, 8, and 9) expression was found to correlate significantly with the key intracellular signaling molecules (MAPKs, NF‐κB/IκB) and higher levels of pro‐inflammatory cytokines including IL‐6 and sTNFR‐1 3, 5, 7, 14, 20, 22, 27, 28, 32, 33. Consistent with earlier in vitro studies, associations with the “adaptive” cytokines (e.g., Th1‐related IFN‐γ, CXCL10/IP‐10, CXCL9/MIG) were also observed, particularly for TLR9 and TLR8, which signal through the MyD88 pathway 3, 4, 10, 34. TLR's active role in cytokine induction was supported by our ex vivo experiments, which showed significant differences in cellular cytokine responses between patients with influenza and controls upon TLR‐specific ligand stimulation (e.g., CpG DNA‐TLR9 and imiquimod‐TLR7; the resultant response pattern governed by the ligand tested, cell type studied, and disease stage at the time of sampling/“immune exhaustion”) and a dynamic change in their responsiveness during clinical recovery 20, 32.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations